Father-absence and the academic achievement of high school students - Nesengani, Ralintho Isaac (School of Education, 2016)
Father-absence, whether it be in the context of short duration or total absence, tends to provide inadequacies in the child's interaction with his/her father, leading to accompanying debilitating effects on cognitive functioning (Sutton-Smith et al, 1986). In view of the South African context father-absence economically sanctioned through migrant labour amongst Africans, manifests itself during the formative years of children's lives. For this reason this study investigates the association between migrant father-absence and children's levels of high school academic achievement. The sample of matched father-absent and -present working class children was acquired from 39 schools under the Venda State department of Education. HSRC's standardised Scholastic Achievement Test (SAT) biology, English second language, and mathematics were used as data gathering instruments. 276 father-absent and -present high school (Std 10) students data was analysed. Analysis of variance (ANOVA) was used to establish how academic achievement among students varies by family patterns and gender. Differences established between family patterns and gender on SAT raw scores of the Total Battery, mathematics, English second language and biology are reported separately. The results of the study seem to suggest that father-absence has some remarkable deleterious effects upon scholastic achievement, apparently depending upon the type of skill tested. Furthermore, another significant finding indicated among these working class African children is that father-presence tends to benefit males more than females, while father-absence detrimentally affects females more than their male counterparts.